The hardware startup : building your product, business, and brand - DiResta, Renee; Forrest, Brady; Vinyard, Ryan (O'Reilly, 2015)
"Validate your idea by learning the needs of potential users; develop branding, marketing, and sales strategies early on; form relationships with the right investment partners; prototype early and often to ensure you're on the right path; understand processes and pitfalls of manufacturing at scale; jumpstart your business with the help of an accelerator; learn strategies for pricing, marketing, and distribution; be aware of the legal issues your new company may face"--Page 4 of cover.